The Serological Diagnosis of Rheumatoid Arthritis: Antibodies to Citrullinated Antigens - Egerer, Karl (Deutscher Arzte Verlag, 2009)
BACKGROUND: This article provides an overview of modern serological diagnostic testing for rheumatoid arthritis (RA) involving the detection of antibodies against citrullinated peptides/proteins (ACPA). Recommendations are also given for differential diagnosis and sequential testing in rheumatoid arthritis, with a view towards improving early diagnosis, so that irreparable joint damage can be avoided. METHODS: Selective literature research, with consideration of the authors’ own publications. RESULTS: Two different, adequately evaluated testing systems, involving the detection of anti-CCP antibodies and of anti-MCV antibodies, are now commercially available and enable routine, relatively highly specific diagnostic testing for RA. Two point-of-care tests (POCT) for the early diagnosis of RA constitute the latest development in serologic diagnostic testing. CONCLUSIONS: The two ACPA assays now on the market are equally useful for the diagnosis of rheumatoid arthritis. The correlation between RA disease activity and stratification with ACPA has only been demonstrated to date through the detection of anti-MCV antibodies.